Wpływ czynników lokalnych na wydatki budżetów powiatów na pomoc społeczną - analiza ekonometryczna - Bal-Domańska, Beata (Influence of Local Factors on Expenditure of District Budgets on Social Welfare - Econometric Analysis, 2007)
Versatile factors influence the level of local authorities expenditure, which in general may be divided into three groups: financial potential, specific local factors influencing the level of costs involved in carrying out services (demographic, economic, infrastructural, environmental) as well as factors resulting from differences in preferences. The article presents research results regarding the influence of selected factors on the level and directions of district expenditure. Panel models, which facilitate incorporating heterogeneous nature of territorial units, were used for the analysis of district budget expenditures.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (18); 2007; nr 1151, s. 110-118